Digital Transformation: An Emphasis Analysis of Enterprise Resource Planning (ERP) Modules in Higher Education - Abdul Rezha Efrat Najaf; Fitri Ana Wati, Seftin; Saka Fitri, Anindo (Information Technology International Journal, 2023)
Industry, and educational institutions in particular, regard digital transformation as a critical information technology. This is due to the fact that educational institutions are required to effectively respond to a multitude of changes, including those associated with digital transformation. This study aims to empirically analyze to the challenges associated with the process of digital transformation, this study examined pertinent scholarly publications, books, and journals. The utilization of the Enterprise Resource Planning (ERP) system in this research endeavors to assess ERP system modules that may be implemented in academic establishments to facilitate the digital transformation process while increasing the efficiency and effectiveness of information resource and technology management. In pursuit of global educational excellence and benchmarks. ERP modules implemented in educational institutions include Competency and Certificate Management, Career Service Management, Student Information Management, Financial and Accounting Management, Asset Management, and E-Learning Management. It is anticipated that the implementation of an ERP system in academic institutions will improve visibility, adaptability, and the capacity to strategize, plan, and operate more effectively. It is crucial to note, however, that many factors must be considered when implementing ERP system modules in academic institutions, including elevated costs, adequate resources, and stakeholder support.